Simplex optimization of carotenoid production by Rhodotorula glutinis using hydrolyzed mung bean waste flour as substrate - Tinoi J. (2014)
The sequential simplex method was employed for the optimization of growth and carotenoid production in the yeast Rhodotorula glutinis using a substrate containing hydrolyzed mung bean waste flour from glass noodle production as the principal nitrogen source and sweet potato extract as the principal carbon source. Six experimental parameters were used: concentration of mung bean waste flour, concentration of sweet potato extract, pH, temperature, agitation rate and cultivation time. Under optimized conditions the cell dry weight was 10.35 ± 0.13 g/l and the total carotenoid content was 3.48 ± 0.02 mg/l using 23.63 g/l of H2SO4-hydroyzed mung bean waste flour, 51.76 g/l of sweet potato extract, pH 5.91, 30.3°C, agitation rate of 258 rpm and incubation time of 94.78 h. These results for cell dry weight and carotenoid content were, respectively, 43 and 20% higher than could be obtained by varying one factor at a time. The present work demonstrates the effectiveness of using a widely available agro-industrial waste product as substrate and the efficiency of the sequential simplex optimization method in obtaining high yields. © 2004 Elsevier Ltd. All rights reserved.